Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.2118/212270-pa
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of In-Situ Combustion Tests on Consolidated and Crushed Cores

Abstract: Summary A significant amount of oil is contained in carbonate reservoirs, but only half of that oil can be produced by secondary enhanced oil recovery (EOR) methods. However, substantial improvements were made in EOR techniques and the prediction of carbonate reservoir performance within the last decades. Nevertheless, existing flow-simulation computer programs failed to provide a reliable prediction of such reservoirs due to their high heterogeneity and the reactivity of the rock. Potentially, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The significant heat losses to the overburden and underburden formations (due to a large temperature gradient) would hinder the achievement of higher temperature values, therefore reducing the amount of dolomite decomposition and CO 2 gas generation. The experimental results of Askarova et al [41] showed lower temperature peaks for the combustion reactions within consolidated dolomites, which is generally the case for reservoirs. Regardless of the magnitude of CO 2 generation in a combustion reaction, the produced CO 2 could be captured and repurposed as an injectant for an EOR application in neighboring reservoirs.…”
Section: Discussionmentioning
confidence: 90%
“…The significant heat losses to the overburden and underburden formations (due to a large temperature gradient) would hinder the achievement of higher temperature values, therefore reducing the amount of dolomite decomposition and CO 2 gas generation. The experimental results of Askarova et al [41] showed lower temperature peaks for the combustion reactions within consolidated dolomites, which is generally the case for reservoirs. Regardless of the magnitude of CO 2 generation in a combustion reaction, the produced CO 2 could be captured and repurposed as an injectant for an EOR application in neighboring reservoirs.…”
Section: Discussionmentioning
confidence: 90%